FEATURES OF PUBLIC-PRIVATE PARTNERSHIP IMPLEMENTATION AT THE REGIONAL LEVEL - Shchur , R.I.; Kropelnytskyi , A.O. (The actual problems of regional economy development, 2023)
Russia's military aggression, which is currently ongoing, has intensified the actualization of the issue of limited financial support of local budgets. To the list of existing problems, such as: outdated infrastructure, neglected state of housing and communal services, low quality of public services, problems of post-war reconstruction and provision, adaptation of temporarily displaced persons were added. The above forces us to look for additional sources for rebuilding infrastructure, creating new jobs, and financing regional socio-economic development projects. One of these sources can be the activation of private capital within the state using the instrument of public-private partnership (PPP). The purpose of the article is the need to carry out further scientific research on the peculiarities of the implementation of public-private partnership at the regional level in the conditions. Achieving the goal is ensured by the use of such methods as analysis and synthesis, generalization and scientific abstraction. Particular attention is paid to the fact that the need to rebuild and reconstruct the infrastructure, restore production and create new jobs requires the involvement of external financing and the activation of private capital within the state. PPP can be one of the effective tools for ensuring interaction between the authorities and private business in domestic realities. The world experience of implementing PPP projects confirms the emergence of a significant synergistic effect of the interaction of government and business at all levels. The above requires a comprehensive analysis of PPP basics, its advantages and key factors, the state of implementation of current projects in Ukraine with the aim of activation and practical, effective application of this tool. It has been proven that PPP can become a powerful lever for the recovery and development of the country's economy, especially in the field of infrastructure construction and modernization. At the same time, the use of this tool is necessary not only at the state and regional level, but in conditions of decentralization, at the level of territorial communities. However, for the effective functioning of the PPP mechanism, in our opinion, it is necessary to first improve the institutional environment by involving expert councils at state and local authorities from representatives of the public, scientists, and representatives of private business. This component can become an accelerator for combining the needs of a specific region, community and initiative on the part of private business.